Learning in and for multi-agency working - Daniels, H; Leadbetter, J; Warmington, P; Edwards, A; Martin, D; Popova, A; Apostolov, A; Middleton, D; Brown, S (2007)
This study addresses the challenges faced by organisations and individual professionals, as new practices are developed and learned in multi-agency work settings. The practices examined in the paper involve working responsively across professional boundaries with at-risk young people. The paper draws on evidence from the Learning in and for Interagency Working Project, a four year ESRC Teaching and Learning Research Programme study of inter-professional learning which has examined the challenges involved in what Victor and Boynton (1998) term co-configuration work. In the context of professional collaboration for social inclusion, co-configuration involves on-going partnerships between professionals and service users to support young people's pathways out of social exclusion. This work demands a capacity to recognise and access expertise distributed across local systems and to negotiate the boundaries of responsible professional action with other professionals and with clients. The paper outlines the activity theory derived theoretical platform adopted by the project and describes the intervention methodology that is being developed, as we study the learning challenges identified by children's services practitioners in UK local authorities.